2017
DOI: 10.1136/bmjgh-2017-000325
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of attrition from care at 2 years in a prospective cohort of HIV-infected adults in Tigray, Ethiopia

Abstract: IntroductionEthiopia has experienced rapid expansion of antiretroviral therapy (ART). However, as long-term retention in ART therapy is key for ART effectiveness, determinants of attrition need to be identified so appropriate interventions can be designed.MethodsWe used data from the ‘Cohort of African people Starting Antiretroviral therapy’ (CASA) project, a prospective study of a cohort of HIV-infected patients who started ART in seven health facilities (HFs). We analysed the data of patients who had started… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 31 publications
8
15
0
Order By: Relevance
“…In the exposed group, attrition was mainly from verified death whereas LTFU was found to be the major cause for attrition in the unexposed group. The later was in agreement with the existing evidence [ 12 , 13 , 20 ]. Different studies indicated that in low resource setting with poor vital registration system like in Ethiopia, deaths, and causes of death are not reported.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the exposed group, attrition was mainly from verified death whereas LTFU was found to be the major cause for attrition in the unexposed group. The later was in agreement with the existing evidence [ 12 , 13 , 20 ]. Different studies indicated that in low resource setting with poor vital registration system like in Ethiopia, deaths, and causes of death are not reported.…”
Section: Discussionsupporting
confidence: 92%
“…The overall Kaplan-Meir estimates of retention show that the largest attrition occurred in the first year. The probability of retention in the unexposed group was comparable with other studies conducted in Ethiopia [ 12 , 13 ]. Retention in care in the exposed groups from the present study seem to be higher than other studies in a similar setting unexposed for mental health care [ 13 , 19 ].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Most (32) of the designs of the primary articles was retrospective follow up [9,10,[16][17][18], five case control [8,[49][50][51][52], six prospective cohort study [37,[53][54][55][56][57][58] and two cross sectional survey designs [59,60]. Every region of Ethiopia was represented in the included studies.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%